2012
DOI: 10.1192/bjp.bp.112.112078
|View full text |Cite
|
Sign up to set email alerts
|

Out-patient psychological therapies for adults with anorexia nervosa: randomised controlled trial

Abstract: Adults with anorexia nervosa are a difficult to treat group. The imbalance between groups in partner relationships may explain differences in service utilisation favouring SSCM. This study confirms SSCM as a useful treatment for out-patients with anorexia nervosa. The novel treatment, MANTRA, designed for this patient group may need adaptations to fully exploit its potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
144
2
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(156 citation statements)
references
References 35 publications
2
144
2
8
Order By: Relevance
“…The degree of BMI change observed in the MOSAIC trial is comparable to that found in our earlier single-centre pilot RCT (total n = 72), which used identical study inclusion criteria and which also compared MANTRA and SSCM, 136 suggesting that these treatments can be disseminated to other UK centres with relatively brief initial training (2 days) of therapists and booster training (1 day).…”
Section: Comparison Of Main Findings With Those Of Other Trialssupporting
confidence: 60%
See 1 more Smart Citation
“…The degree of BMI change observed in the MOSAIC trial is comparable to that found in our earlier single-centre pilot RCT (total n = 72), which used identical study inclusion criteria and which also compared MANTRA and SSCM, 136 suggesting that these treatments can be disseminated to other UK centres with relatively brief initial training (2 days) of therapists and booster training (1 day).…”
Section: Comparison Of Main Findings With Those Of Other Trialssupporting
confidence: 60%
“…A treatment workbook is given to each patient (see data supplement DS1 in Schmidt et al 126,136 for details). This has both core and optional chapters, thus the information contained in the manual can be tailored to the requirements of each patient.…”
Section: Maudsley Model Of Anorexia Nervosa Treatment For Adultsmentioning
confidence: 99%
“…SSCM is derived from the typical supportive approach of specialists to the management of AN. Both studies showed sustained improvements in eating disorder features and weight and no significant differences between MANTRA and SSCM (McIntosh et al, 2005;Schmidt et al, 2012;Touyz et al, 2013). In the first of these RCTs (Schmidt et al, 2012) the mean BMI increase from baseline to 12 months post-randomization (end of treatment) for MANTRA and SSCM respectively was 1.37 kg/m 2 and 1.22 kg/m 2 .…”
mentioning
confidence: 99%
“…Both studies showed sustained improvements in eating disorder features and weight and no significant differences between MANTRA and SSCM (McIntosh et al, 2005;Schmidt et al, 2012;Touyz et al, 2013). In the first of these RCTs (Schmidt et al, 2012) the mean BMI increase from baseline to 12 months post-randomization (end of treatment) for MANTRA and SSCM respectively was 1.37 kg/m 2 and 1.22 kg/m 2 . In the later multi-centre RCT (the MOSAIC Study; Schmidt et al, 2015), the mean BMI increase at the same time point was 1.75 kg/m 2 for MANTRA and 1.36 kg/m 2 for SSCM.…”
mentioning
confidence: 99%
See 1 more Smart Citation